A Porphyrin Complex as a Self‐Conditioned Electrode Material for High‐Performance Energy Storage - Gao, Ping; Chen, Zhi; Zhao‐Karger, Zhirong; Mueller, Jonathan E.; Jung, Christoph; Klyatskaya, Svetlana; Diemant, Thomas; Fuhr, Olaf; Jacob, Timo; Behm, R. Jürgen; Ruben, Mario; Fichtner, Maximilian (Angewandte Chemie International Edition, 2017)
The novel functionalized porphyrin [5,15‐bis(ethynyl)‐10,20‐diphenylporphinato]copper(II) (CuDEPP) was used as electrodes for rechargeable energy‐storage systems with an extraordinary combination of storage capacity, rate capability, and cycling stability. The ability of CuDEPP to serve as an electron donor or acceptor supports various energy‐storage applications. Combined with a lithium negative electrode, the CuDEPP electrode exhibited a long cycle life of several thousand cycles and fast charge–discharge rates up to 53 C and a specific energy density of 345 Wh kg−1 at a specific power density of 29 kW kg−1. Coupled with a graphite cathode, the CuDEPP anode delivered a specific power density of 14 kW kg−1. Whereas the capacity is in the range of that of ordinary lithium‐ion batteries, the CuDEPP electrode has a power density in the range of that of supercapacitors, thus opening a pathway toward new organic electrodes with excellent rate capability and cyclic stability. Give and take: Electrodes based on a copper porphyrin showed excellent capacity retention over several thousand cycles and very fast charge–discharge rates, thus opening a pathway to organic electrode materials with the capacity of a lithium‐ion battery and the rate capability of a good supercapacitor. The ability of the porphyrin complex to serve as an electron donor or acceptor is advantageous for various energy‐storage applications (see picture).